2009
DOI: 10.1152/ajpheart.00802.2009
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous variation of ventricular pacing site and timing with biventricular pacing in acute ventricular failure improves function by interventricular assist

Abstract: The goal of this work was to investigate the hemodynamic effects of simultaneous left ventricular (LV) pacing site (LVPS) and interventricular pacing delay (VVD) variation with biventricular pacing (BiVP) during acute LV failure. Simultaneously varying LVPS and VVD with BiVP has been shown to improve hemodynamics during acute right ventricular (RV) failure. However, effects during acute LV failure have not been reported. In six open-chest pigs, acute LV volume overload was induced by regurgitant flow via an ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…We have previously described animal models of acute right- and left-sided heart failure and found BiVP to be beneficial in those settings 32-34. The mechanism of action appears to be synchronization of pressure development across the interventricular septum, which allows the less impaired ventricle to assist the failing one 34. These findings provide further rationale for studying temporary BiVP in the perioperative setting and will serve as a guide for future studies examining the mechanism behind the effect demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described animal models of acute right- and left-sided heart failure and found BiVP to be beneficial in those settings 32-34. The mechanism of action appears to be synchronization of pressure development across the interventricular septum, which allows the less impaired ventricle to assist the failing one 34. These findings provide further rationale for studying temporary BiVP in the perioperative setting and will serve as a guide for future studies examining the mechanism behind the effect demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported pressure-volume loops during BiVP without optimization [18,26]. Our laboratory studies suggest that BiVP can synchronize pressure development across the interventricular septum, bringing pressure work from the less compromised ventricle to the assistance of the distressed ventricle [35]. Those studies did not involve cardioplegia and cardioplegic arrest, however.…”
Section: Commentmentioning
confidence: 93%
“…LV1 was used preferentially during phase I. An InSync III biventricular pacemaker (Medtronic, Inc, Minneapolis, MN) was used for pacing and electromagnetic (Carolina Medical Electronics, East Bend, NC) or ultrasonic (Transonics Systems Inc, Ithaca NY) probes measured aortic flow [35–37]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, a number of preclinical studies have shown BiVP improves hemodynamics in acute volume and pressure overload states when atrioventricular (AVD) and ventriculoventricular delays (VVD) are varied to directly optimize hemodynamics despite normal ventricular electrical conduction and contractility. 4,5 This model of BiVP was adapted to the post-cardiopulmonary bypass state to act as an adjunct to inotropes or vasopressors. In the Biventricular Pacing After Cardiac Surgery Trial, it was shown that this technique can improve hemodynamics in the first hours after bypass 6,7 and postoperative day 1 in patients who underwent aortic valve replacement.…”
mentioning
confidence: 99%